1994
DOI: 10.1039/jm9940400805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-modelling studies of the polypropylene catalyst

Abstract: Polypropylene is formed using a catalyst typically consisting of TiCI, supported on a MgCI, substrate. A Combination of molecular-modelling methods has been used to investigate the catalyst at the atomic level. Molecular graphics and static lattice calculations show that MgCI, exhibits stable surfaces in which surface Mg ions are four, five and six coordinated. Density functional theory calculations show that TiCl, binds to MgCI2 via a 'triply bound' model. This results in one of the CI-Ti-CI bond angles openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…This plane is most likely to be the (100) plane, which is the second most stable plane of the crystal. 44,45 By assuming this structural information to be applicable to the model catalyst films, we could attribute the dominant mesitylene desorption peak at ¾200 K for TiCl x /MgCl 2 to a basal plane structure where the chlorine ions at the outermost layer are close packed and the metal ions under the chlorine layer are coordinated to six chlorine atoms. 20 In this frame, the high-temperature desorption peak at 246 K could be attributed tentatively to a non-basal plane where the surface chlorine ions are not close packed and the metal ions under the chlorine layer are under-coordinated.…”
Section: The Ticl Y Multilayer Film As a Model System For The Ticl 3 mentioning
confidence: 99%
See 2 more Smart Citations
“…This plane is most likely to be the (100) plane, which is the second most stable plane of the crystal. 44,45 By assuming this structural information to be applicable to the model catalyst films, we could attribute the dominant mesitylene desorption peak at ¾200 K for TiCl x /MgCl 2 to a basal plane structure where the chlorine ions at the outermost layer are close packed and the metal ions under the chlorine layer are coordinated to six chlorine atoms. 20 In this frame, the high-temperature desorption peak at 246 K could be attributed tentatively to a non-basal plane where the surface chlorine ions are not close packed and the metal ions under the chlorine layer are under-coordinated.…”
Section: The Ticl Y Multilayer Film As a Model System For The Ticl 3 mentioning
confidence: 99%
“…41 The LEED study of a MgCl 2 film deposited by thermal evaporation in UHV showed that the film grows layer by layer and the film surface was composed of small domains of the (001) basal plane, the most stable crystallographic plane. 39,44,45 The He C ISS studies of the model Ziegler-Natta catalyst films found that the surfaces of these films are terminated with chlorine ions and no metal ions are exposed to the vacuum. 9,10,12 The SEM pictures described the TiCl 3 microcrystallites produced by a sublimation-recrystallization method as possessing a very thin, hexagonal platelet shape.…”
Section: The Ticl Y Multilayer Film As a Model System For The Ticl 3 mentioning
confidence: 99%
See 1 more Smart Citation
“…The next most stable surface structures are the (100) and (110) planes of the rhombohedral crystal structure. Although the metal ion is partially exposed in these planes, the chloride ion arrangement around the metal ion does not have the correct symmetry to produce isotactic polypropylene (11). The thermodynamics of the chloride compound structure therefore render it difficult to obtain the open and specific ligand structure around the active metal ion needed for preparation of the single-site polymerization site.…”
Section: Strategy For Preparation Of Single-site Heterogeneous Zieglementioning
confidence: 99%
“…1b). For these compounds, the thermodynamically most stable surface is the (001) basal plane of the rhombohedral crystal structure (9,11). This surface is terminated with a close-packed chloride layer and the metal ion is shielded beneath this chloride layer (12)(13)(14).…”
Section: Strategy For Preparation Of Single-site Heterogeneous Zieglementioning
confidence: 99%